Peranan Komite Sekolah dalam Mendukung Proses Kegiatan Belajar Mengajar di Sekolah - Somali, Soni Gunawan; Parsono, Slamet; Yudhakusuma, Dudi (Jurnal Pengabdian Tri Bhakti, 2021)
The school committee is an independent institution that is formed and plays a role in improving the quality of services by providing consideration, direction and support for personnel, facilities and infrastructure, as well as education supervision at the education/school unit level. The purpose of the establishment of the school committee is to accommodate the participation of stakeholders/parents/community to participate in school management operations in accordance with their roles and functions, with regard to planning, implementing and evaluating school programs in a proportional manner, so that school committees can improve transparent education management. and accountable. The purpose of establishing the school committee is also intended to have a school community organization that has commitment and loyalty and cares about improving the quality of schools. The successful implementation of education is not only the responsibility of the central government, but also local governments (provinces, districts and cities), schools, parents, and the community or education stakeholders. The existence of school committees in education/school units will work effectively if there is an understanding of school committee administrators and school principals on the duties and roles of school committees as well as active participation of school committees in implementing school activity programs.